2021
DOI: 10.1186/s13690-021-00584-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical activity and postural habits in schoolchildren with scoliosis

Abstract: Background Scoliosis is considered one of the main musculoskeletal changes in childhood, and is characterized by three-dimensional changes in the spine. Schoolchildren is a group who are directly exposed to this condition because they go through a rapid growth phase in adolescence, added to other external factors such as school environment and daily living habits such as little physical activity. This study aimed to identify the risk factors associated with scoliosis in schoolchildren. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
(42 reference statements)
2
12
0
Order By: Relevance
“…The assessment revealed that diseases of the musculoskeletal system and connective tissue constantly held the 1 st rank place in the structure of morbidity among 4 th grade children as well as middle and senior school children. These results are in line with data provided by foreign and domestic researchers [2,3,[16][17][18][19][20][21].…”
Section: __________________________supporting
confidence: 91%
See 1 more Smart Citation
“…The assessment revealed that diseases of the musculoskeletal system and connective tissue constantly held the 1 st rank place in the structure of morbidity among 4 th grade children as well as middle and senior school children. These results are in line with data provided by foreign and domestic researchers [2,3,[16][17][18][19][20][21].…”
Section: __________________________supporting
confidence: 91%
“…Hypodynamia is another behavioral aspect that exerts negative influence on the musculoskeletal system. Physical activity is known to improve blood supply and to activate osteoblast functioning, protein synthesis, calcification, and bone tissue metabolism [15,16]. 60.5 % schoolchildren from Gymnasium were quite committed to doing sports since they did physical exercises or sport from 4 to 7 times a week whereas most schoolchildren from School (76.0 %) attended sports clubs or did physical exercises less than 3 times a week.…”
Section: T a B L E 1 Average Chemical Concentrations Inside Classroomsmentioning
confidence: 99%
“…Since the majority of adolescents, in particular girls, do not meet the current guidelines on physical activity [ 17 ], we presume that lifestyle trends (increased screen time, physical inactivity, and sedentary behavior) are the leading culprits. The association between low physical activity and scoliosis was described in a recent study [ 18 ], in which the FBT was used to assess scoliosis. The observed gender difference may be due to the fact that boys are more involved in sports and physical activity while girls prefer a more sedentary lifestyle, the trend noted in the latest Croatian Health Behaviour in School-aged Children survey in 2017/2018 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some factors may influence the upper body posture as behavioral habits, school and homework routine, time spend on mobile device, posture adapted to carry school bag (Cejudo, 2022;da Rosa et al, 2022;Popescu & Lee, 2020;Vaterlaus et al, 2021). Although sports training might have some disadvantageous effects on posture, it is essential to emphasize the positive influence of physical activity on physical fitness of children and youth, which has been documented by numerous authors (Tomaczkowski & Klonowska, 2020;de Assis et al, 2021;Xing & Popik, 2020;Opala-Berdzig et al, 2021).…”
Section: Discussion and Limitsmentioning
confidence: 96%